Imaging of Cardiac Aneurysms. (15th September 2018) - Wahl, Daniel R.; Yoon, Susan; Chan, Cynthia; Goykhman, Igor; Hochhold, John; Son, Hongju
Abstract : Cardiac aneurysms are uncommon, encompass a wide variety of pathologies, and can occur in several locations in the heart. Cardiac aneurysms are of varying clinical concern, with some warranting prompt attention and many others with no clinical significance. Cardiac aneurysms may be identified on electrocardiogram-gated CT or MRI and incidentally on nongated imaging examinations. As CT and MRI are requested increasingly to evaluate anatomic cardiac pathology, radiologists should become familiar with the imaging appearances, clinical significance, and management options of cardiac aneurysms.